Inside the Primary Classroom: 20 Years On - Comber, Chris (Routledge, 1999)
In recent years primary education has been the subject of continuing debate with questions of standards and their apparent decline being raised with alarming regularity. Central in informing these debates has been the ORACLE study of groupwork in primary classrooms. Published during the 1980s, the study described in detail the daily life of the primary classroom, the teaching styles used by teachers and the responses of pupils. That research has now been replicated - with over two thirds of the schools originally studied being revisited, using the same tests and observation instruments. This book presents the findings of this second round of research, and is therefore unique in being able authoritatively to document the changes - or lack of them - in primary education and teaching practice over the last twenty years.